P157 A nurse-led new entrant latent TB infection screening clinic- the Croydon experience. (11th November 2022) - Gasmelseed, MMI; Scott, M; Soobratty, MR; Booysen, J; Camara, J; Lacle, J; Chaudhry, S; Raste, Y
Abstract : Introduction: Although overall TB incidence in Croydon is 18/10000, there are wards with higher rates (40–79/100000 1 ). There is dynamic influx of people from high incidence countries, especially due to the location of immigration services. Screening this high-risk group for LTBI is essential. We present a successful nurse-led LTBI screening service centrally funded by UKHSA. Method: Individuals were identified through NHS Flag 4 data (international in-migrants at new GP registration) between October 2019 to March 2022. 2 They had to be aged 16–35 years, have entered the UK within the past five years, never been a UK resident and have lived in a high TB incidence country for at least 3 months to be eligible for screening. Patients were invited to a nurse-led appointment where clinical history, CXR and IGRA were obtained. Results: 2525 individuals were invited for screening, 735 attended (29%), 147 were diagnosed with LTBI (20%), with 7 cases of active TB. Interestingly, 15 cases of active TB identified in the clinic had been invited through the programme but did not attend. Prior to the COVID-19 pandemic (October 2019-March 2020), there was a 52% attendance rate (522 screened, 269 attended). The service was suspended from late March-June 2020 and January –March 2021; attendance rate was poor throughout 2020 at 15.6% (1144 screened, 178 attended). To improve attendance, a leaflet about the screening programme was sent prior to appointment letters, which improved the rate to 46% in 2021 (584 screened, 269 attended). Discussion: Of those who attended, the LTBI rate was 20%, highlighting the importance of targeted population screening. Early identification prevents some cases developing active TB. 7 active TB cases were identified early, with improved patient outcomes and reduced contacts. Limitations are the poor uptake, partly due the COVID-19 pandemic (service suspension). Barriers include language (non-English speakers); lack of understanding about latent TB; stigma associated with TB; financial constraints; and temporary accommodation of this population, hence difficulty arranging appointments. Leaflets in different languages and work with community and religious leaders would help to raise awareness. References: Tuberculosis in England 2021 report – UK Health Security Agency https://www.england.nhs.uk/tuberculosis-programme/area-for-action-8-national-latent-tb-infection-testing-and-treatment-programme/